Development of support software for inclusive online education (Journal of Educational Sciences, 2021)
Situation with coronavirus has demonstrated that online education is a compulsory measure in arrangement of education for children with disabilities. Learners with disabilities cannot capture educational programs without use of dedicated (adapted) educational programs and methods of teaching and upbringing and also their software support. This article covers issues of arrangement of an educational process for learners with mental retardation with the use of online educational technologies and also describes experience of creation of ‘InclusiveEdu – Information Science 7’ software within principal educational school program. It offers maximum available and efficient educational space arrangement of which takes into account individual characteristics of learners and this educational space can involve all the participants in educational relations: learners, their parents (legal representatives), teachers, special community helpers. It has been found that mentally-retarded children prefer to watch and listen to information instead of reading. That is why the developed software product offers an opportunity to listen to important information. In order to test efficiency of the developed software, a pedagogical experiment was carried out in four schools of Almaty City in conditions of online education which produced positive results in favor of the offered teaching methodology.Key words: online education, inclusive education, inclusive online education, software, disabilities, mental retardation, dedicated educational programs, special educational needs.